2007
DOI: 10.1016/j.jtcvs.2007.03.030
|View full text |Cite
|
Sign up to set email alerts
|

Expanded polytetrafluoroethylene valved conduit and patch with bulging sinuses in right ventricular outflow tract reconstruction

Abstract: The expanded polytetrafluoroethylene valved conduits and patches with bulging sinuses showed excellent early-to-midterm results. The valved conduits and patches seem to be promising alternatives to homografts in right ventricular outflow tract reconstruction. Their function will be followed up further.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
60
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 70 publications
(60 citation statements)
references
References 24 publications
0
60
0
Order By: Relevance
“…1) Various materials have been used for RVOT reconstruction to achieve successful long-term results, i.e., avoiding PR and consequent right ventricular failure. 6) We have designed a fan-shaped expanded polytetrafluoroethylene-valved conduit and patch with bulging sinuses for greater long-term durability and reliability. 6) These valved conduits and patches have functioned well, retaining low-pressure gradients at the valves and minimum PR for up to 5 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1) Various materials have been used for RVOT reconstruction to achieve successful long-term results, i.e., avoiding PR and consequent right ventricular failure. 6) We have designed a fan-shaped expanded polytetrafluoroethylene-valved conduit and patch with bulging sinuses for greater long-term durability and reliability. 6) These valved conduits and patches have functioned well, retaining low-pressure gradients at the valves and minimum PR for up to 5 years.…”
Section: Discussionmentioning
confidence: 99%
“…6) We have designed a fan-shaped expanded polytetrafluoroethylene-valved conduit and patch with bulging sinuses for greater long-term durability and reliability. 6) These valved conduits and patches have functioned well, retaining low-pressure gradients at the valves and minimum PR for up to 5 years. To prevent delayed pulmonary problems, many surgical modifications for preserving the pulmonary valve as well as pulmonary annulus have also been developed.…”
Section: Discussionmentioning
confidence: 99%
“…The hemisphere-shaped bulging sinuses, 3 mm in depth, were formed on the conduit wall. Fan-shaped leaflets were cut out from an ePTFE pericardial sheet and sutured along the curved bottom suture lines in the bulging conduit [14]. The lea et cusps and bulging sinuses were xed on the conduit wall by ePTFE suture.…”
Section: Pulmonary Heart Valves Testedmentioning
confidence: 99%
“…The RVOT reconstruction is commonly performed as a surgical treatment for congenital heart diseases with pulmonary coarctation, to decrease right ventricular afterload and to promote pulmonary arterial blood ow. Initial clinical studies of the ePTFE valve reported excellent early-to-midterm results [14,16]. A report suggested that surgical strategy using the ePTFE valve may promote patients circulatory conditions and contribute to the elimination of reoperation as well as the prevention of pulmonary insuf ciency [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation